PELATIHAN APLIKASI BAGI HASIL TABUNGAN MUDHARABAH PADA KOPERASI MADRASAH ALIYAH AL-INAYAH BANDUNG - Muhammad Muflih; Radia Purbayati; Hasbi Assidiki; Destian Arshad (Bahasa Indonesia, 2022)
Currently, the Madrasah Aliyah Al-Inayah Bandung Cooperative requires the implementation of mudharabah profit-sharing savings based on electronic applications to improve the quality of savings services. The fundamental problem of this cooperative is the absence of knowledgeable human resources in the field of saving for the results of mudharabah and the low number of supporting facilities for these savings operations. These competencies and facilities can increase the absorption of funds from the community. In addition, the number of people in the cooperative environment is large and has the potential to grow these savings in the future. For this reason, the community service program (PkM) for mudharabah savings management training needs to be present to answer this issue. This program involved 15 participants who came from the management of the MA Al-Inayah Cooperative. The training materials consist of; (1) knowledge of mudharabah profit-sharing procedures, (2) digital mudharabah profit-sharing management applications, and (3) applications that support the operating system for sharia cooperative profit-sharing mudharabah savings results. This training program has succeeded in increasing the capability of the management of the MA Al-Inayah Cooperative in operating an electronic application for mudharabah profit-sharing savings so that it has an effect on the suitability of the cooperative with the latest technological developments and improving the quality of services that are fast, accurate, and productive. On that basis, PkM like this deserves to be developed in other sharia cooperatives so that they are adaptive to technology and competitive. Abstrak Pelaksanaan tabungan bagi hasil mudharabah berbasis aplikasi elektronik sangat dibutuhkan Koperasi Madrasah Aliyah Al-Inayah Bandung untuk meningkatkan kualitas layanan tabungan. Permasalahan mendasar koperasi ini adalah ketiadaan SDM yang berpengetahuan di bidang tabungan bagi hasil mudharabah dan rendahnya fasilitas penunjang operasional tabungan tersebut. Padahal, kompetensi dan fasilitas ini sangat penting untuk peningkatan penyerapan dana yang berasal dari masyarakat. Di samping itu, jumlah masyarakat di lingkungan koperasi tersebut banyak dan berpotensi menumbuhkembangkan tabungan ini di masa depan. Untuk itulah, pengabdian kepada masyarakat (PkM) yang menyelenggarakan pelatihan manajemen tabungan bagi hasil mudharabah sangat penting menjawab persoalan ini. Dengan melibatkan 15 pengurus Koperasi MA Al-Inayah sebagai peserta, PkM ini melatih tiga hal penting, yaitu; (1) pengetahuan prosedur bagi hasil mudharabah, (2) kemampuan mengaplikasikan manajemen tabungan bagi hasil mudharabah secara digital, dan (3) penyediaan aplikasi yang menunjang sistem operasional bagi hasil tabungan mudharabah level koperasi syariah. Program pelatihan ini berhasil meningkatkan kapabilitas pengurus Koperasi MA Al-Inayah dalam mengoperasikan aplikasi elektronik tabungan bagi hasil mudharabah sehingga berefek terhadap kesesuaian koperasi tersebut dengan perkembangan teknologi mutakhir dan peningkatan kualitas layanan yang cepat, akurat, dan produktif. Atas dasar itulah, PkM seperti ini layak dikembangkan di koperasi-koperasi syariah lainnya agar mereka adaptatif terhadap teknologi dan kompetitif.